Distinctive clinical patterns and management trends in late-onset psoriatic arthritis: data from Argentina’s RECCAPSO registry - Gustavo A. Medina; Maximiliano Fenucci; Sebastián Magri; Marcelo Abdala; Tamara Arias; Brian Abdala; Leila Abbas; Vinod Chandran; Rodrigo García-Salinas (Therapeutic Advances in Musculoskeletal Disease)
Background: Late-onset psoriatic arthritis (LO-PsA) has been underexplored despite its growing prevalence in aging populations. Understanding its distinct clinical presentation and treatment patterns is essential to optimize care in this subgroup. Objectives: To describe the demographic, clinical, and therapeutic features of patients with LO-PsA compared to early onset PsA (EO-PsA) using data from the Argentine RECCAPSO registry. Design: Ambispective, multicenter analysis with a cross-sectional evaluation. Methods: Patients with PsA were categorized into EO-PsA (age of onset ⩽60 years) and LO-PsA (>60 years). Demographics, clinical characteristics, disease activity, and treatment variables were compared between groups using appropriate statistical tests. A multivariate logistic regression model was constructed to identify factors independently associated with LO-PsA. Results: A total of 271 PsA patients were included (EO-PsA: n  = 184; LO-PsA: n  = 87). LO-PsA patients had higher frequencies of hypertension (50% vs 21.4%, p  < 0.001), diabetes (22.1% vs 7.9%, p  = 0.007), and oligoarticular presentation (57.4% vs 40.5%, p  = 0.03), and were less likely to receive b/tsDMARDs (42.6% vs 58.7%, p  = 0.02). In multivariate analysis, hypertension (OR: 4.69, 95% CI: 1.83–12.03) and diabetes (OR: 14.83, 95% CI: 2.36–93.05) were independently associated with LO-PsA. Conclusion: LO-PsA presents a distinct clinical profile characterized by greater comorbidity burden and lower exposure to advanced therapies. These findings highlight the need for tailored management strategies in older adults with PsA.